IMPLEMENTATION OF MANAGEMENT INFORMATION SYSTEMS IN SALES PERFORMANCE AT CAFE HANAMI - Andara Rahmadanti Pulungan; Arif Rahman; Ryndian Gusty; Syafri Naldi; John Sihar Manurung; Safaruddin Safaruddin (CV. Visionary Raya Sakti, 2026)
This research aims to deeply analyse the implementation of the sales management information system (SIM) in Hanami Cafe as a real form of digitalisation efforts carried out by micro businesses in the culinary sector. In the face of the era of rapid digital transformation, the use of information systems is an important aspect for small businesses to increase their efficiency and operational effectiveness. This research uses a qualitative approach by combining in-depth interview methods and direct observation of the owners and employees of Hanami Cafe to obtain accurate and comprehensive data. The main focus of the research includes several aspects, including the effectiveness of the use of information systems in sales activities, the level of understanding and training received by employees, the stock management system, the sales transaction process, and various obstacles that arise during the system implementation process. Through the results of the research obtained, it is known that the implementation of the management information system at Hanami Cafe has a positive impact on improving the efficiency of transaction recording, ease of managing raw material stock, and accuracy in operational decision making. Based on the findings, this research emphasises the importance of developing a comprehensively integrated management information system for small businesses such as Hanami Cafe. The implementation of a good information system not only supports operational efficiency, but also becomes an important foundation in strengthening competitiveness and business sustainability in the current digital era.